Age-Dependent DNA Methylation Variability on the X-Chromosome in Male and Female Twins - Qihua Tan; Hikmat Alo; Marianne Nygaard; Mette Sørensen; Alisa Saleh; Jonas Mengel-From; Kaare Christensen (Epigenomes)
We aimed to explore the age-dependent epigenetic variability on the X-chromosome with consideration of X-chromosome inactivation by applying a sex-stratified regression analysis to DNA methylation array data on X-linked CpGs in aging identical twins. We found 13 X-linked CpGs showing age-related significant increase in variability in males (FDR < 0.05) but none in females. In females, we found a significantly higher proportion of CpGs showing increased variability with age among nominally significant (p < 0.05) CpGs under inactivation, but not among CpGs escaping inactivation. Survival analysis showed a slight trend of correlation by directional change in the variable CpGs with mortality in males. Compared with females, the male X-chromosome can be more vulnerable to epigenetic instability during aging.